Immunocytochemistry of In vitro produced mucin from HT29- MTX cell line - Immunocytochemistry of In vitro produced mucin from HT29- MTX cell line (Institute of Medico-legal Publications Pvt Ltd, 2020)
Mucus represents the first line of defense against pathogens and damage in the human intestine. the majorcomponents of mucus are mucins which are high molecular weight glycoproteins providing potential bindingsites for both pathogenic and commensal microorganisms. To study host-enteric pathogen interactions,human intestinal cell models are widely used. Epithelial cell lines derived from human colon carcinomasproviding useful experimental alternatives as getting normal intestinal cells is not easily applicable.In the current study, we described a condition enhances HT29-MTX cells to produce continuous mucuslayer. Immunocytochemistry was used to visualize Muc 2, the most secreted mucin from HT29-MTX cellsusing anti Muc2 antibody.The results showed that incubation of HT-29 MTX cells with shaking and providing cells with fresh mediumonce to twice daily for three weeks can be the best way to mimic the natural behavior of the intestine whichenhanced the seeded cells to produce the mucin in vitro.